2009
DOI: 10.1002/ptr.2931
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of healing and antimicrobiological effects of herbal therapy on venous leg ulcer: pilot study

Abstract: Venous leg ulcers represent a significant public health problem that will increase as the population ages. Numerous herbs and their extracts are potentially conducive to wound healing, including the ability to serve as an antimicrobial, antifungal, astringent, etc. A total of 32 patients with venous leg ulcers were randomized into two groups: a group with herbal therapy treatment (PT) (17 patients) and a control group (C) (15 patients). The investigation focused on five controls of parameter changes important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…Huseini et al (2005) tested a seven-species product called Liv-52 in cirrhosis patients and found significant benefit; however, the small number of patients involved in the trial (a total of 36 in both arms) means that results cannot be taken as conclusive. Likewise, Binić et al (2010), also in a pilot study with few patients, reported that a three-herb topical preparation including yarrow healed surface and venous leg ulcers, outperforming a topical antibiotic.…”
Section: Clinical Trialsmentioning
confidence: 95%
“…Huseini et al (2005) tested a seven-species product called Liv-52 in cirrhosis patients and found significant benefit; however, the small number of patients involved in the trial (a total of 36 in both arms) means that results cannot be taken as conclusive. Likewise, Binić et al (2010), also in a pilot study with few patients, reported that a three-herb topical preparation including yarrow healed surface and venous leg ulcers, outperforming a topical antibiotic.…”
Section: Clinical Trialsmentioning
confidence: 95%
“…Binić et al, 2010 [66] RCT not blind 17 patients in experimental group and 15 patients in control group.…”
Section: Marigold (Calendula)mentioning
confidence: 99%
“…Binic et al presents the data of its pilot study RCT where 17 patients were treated with herbal therapies compared to 15 patients treated with topical antibiotics [66]. The ulcers of venous leg healed after seven weeks of treatment (p<0.05) and the number of different types of isolated bacterial species decreased.…”
Section: Herbal Therapiesmentioning
confidence: 99%
“…Cineol, tannin, and proazulene from yarrow calm inflammatory processes and help regeneration. Essential oils of sage have antibiotic effects and increase the phagocytic activity of leucocytes which partly affects wound healing [11][12][13]. Extract of marigold acts favourably on wound healing due to a synergistic action between essential oils, xanthophylls, saponins, and flavonoids.…”
Section: Methodsmentioning
confidence: 99%
“…Fitoven ® herbal gel, which contains alcoholic extracts of Aesculus hippocastanum, Melilotus officinalis, Rosmarini, and Lavandulae, is used in the treatment of varicose veins, chronic venous insufficiency, thrombophlebitis, haematomas, and haemorrhoids. Favourable actions of these herbal preparations on wound healing, antibacterial effects, high inhibitory effects on the production of hydroxyl radicals (OH) are described in different pharmacognostic, pharmacological, and phytochemical studies [11][12][13]. The aim of this pilot study was to evaluate healing and antimicrobiological effects of a combined treatment of electro-ionizing radiation, polarized light, and phytotherapy for venous leg ulcers.…”
mentioning
confidence: 99%